Pluralisme, Demokrasi dan Keadilan Sosial dalam Konsepsi Fiqih Humanistik Abou el Fadl - Abid Rohmanu (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2009)
To make connection between fiqih and humanism is often judged as a subversive. Religion is convinced the only source of morality, then rationality tendency to discover morality ? such as humanism - never get a proportional place. Whereas at a certain point religioun is meaned totalitarianly by his follower, there?s potency to exploit religion for political and partisan interest that will kill humanistic values. In this context, the existence of religion is important to be reflected in a humanization process, namely a process to place and treat human being more human. From the above frame work, this assignment will explain the Abou El Fadl?s conception of humanistic fiqih related to pluralism, democracy, and social justice. These three conceptions are ?par excellence? humanistic values that often being campaigned by Abou El Fadl. Abou El Fadl is a scholar who has great attention to establish link between Islam, fiqih and morality.